2022
DOI: 10.1007/s00705-022-05602-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, reassortment, and recombination of mammalian orthoreoviruses from Japanese porcine fecal samples

Abstract: Mammalian orthoreovirus (MRV) is a non-enveloped double-stranded RNA virus with a broad host range. MRVs are prevalent worldwide and have been isolated from various hosts, including humans, dogs, cats, wild boars, sewage, and pigs, in Japan. However, Japanese porcine MRV has not been genetically characterized yet. While investigating porcine enteric viruses including MRV, five MRVs were isolated from the feces of Japanese pigs using the MA104 cell culture. Genetic analysis of the S1 gene revealed that the Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The μB protein tended to be conserved to a similar degree as the core proteins as observed previously for other orthoreoviruses ( 5 , 29 ). Furthermore, in the comparison with MAHLV we found identity values above the demarcation criteria defined for distinct species for three additional sequences (λB 65.76–66.72% aa; λA 60.37–62.23% nt; and λB 62.37–63.98% nt identity) confirming the tree topologies where MAHLV appeared to be the closest relative of reptile origin orthoreoviruses ( 27 , 30 , 31 ).…”
Section: Resultssupporting
confidence: 73%
“…The μB protein tended to be conserved to a similar degree as the core proteins as observed previously for other orthoreoviruses ( 5 , 29 ). Furthermore, in the comparison with MAHLV we found identity values above the demarcation criteria defined for distinct species for three additional sequences (λB 65.76–66.72% aa; λA 60.37–62.23% nt; and λB 62.37–63.98% nt identity) confirming the tree topologies where MAHLV appeared to be the closest relative of reptile origin orthoreoviruses ( 27 , 30 , 31 ).…”
Section: Resultssupporting
confidence: 73%
“…The serotypes were classified into 4 types (MRV1 to 4, respectively) based on the S1 segment [4]. MRV1 to 3 serotypes were isolated from pigs in worldwide [8,16,17,19,39] including Japan [6,7,11]. Some studies have shown that MRVs isolates caused severe symptoms and mortality in experimentally infected piglets and pigs [32,36], which means that MRVs have the potential to cause serious problems on swine industry.…”
Section: Introductionmentioning
confidence: 99%
“…Although data on the surveillance in pig farms can help to control MRVs infection among pigs, the surveillance report in Japan is limited. The latest report showed that five MRVs were isolated from 230 porcine feces in Japan [6].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the RNAs were treated with DNase I (Takara Bio), and cDNA libraries were constructed using an NEBNext Ultra II RNA Library Prep Kit for Illumina (New England Biolabs, Ipswich, MA, USA), as described previously [5]. However, a sufficient number of Bo_ ParV-specific sequence reads were not obtained.…”
mentioning
confidence: 99%
“…qRT-PCR-positive samples were subjected to virus isolation using MA104 cells as described previously [5]. Extensive cytopathic effect appeared in the MA104 cells two or three days after inoculation at the second or third passages.…”
mentioning
confidence: 99%